Calculated Characteristics of a Transistor Laser Using Alloys of Gr‐IV Elements. Issue 9 (29th July 2018) - Mukhopadhyay, Bratati; Sen, Gopa; De, Souradeep; Basu, Rikmantra; Chakraborty, Vedatrayee; Basu, Prasanta K.
Abstract : The performance of a transistor laser (TL) structure consisting of SiGeSn emitter, SiGeSn base incorporating a GeSn quantum well (QW) and a GeSn collector is studied in the present work. The Sn concentration is chosen to yield direct band gap for all the layers. An earlier model developed for InGaAs QW in GaAs base, that could satisfactorily explain most of the experimental data, is employed to calculate terminal currents, threshold current, and light power output. The model solves continuity equation, considers virtual states above QW, Fermi Golden rule to calculate gain, Fermi statistics for occupancy of subbands and broadening of states. A low value of threshold base current is predicted. Abstract : The performance of a transistor laser (TL) structure consisting of SiGeSn emitter, SiGeSn base incorporating a GeSn quantum well (QW) and a GeSn collector is studied in the present work. The lower threshold base current in GeSn base TL may allure workers to fabricate and characterize transistor lasers using alloys of group‐IV semiconductors.